STAR 3G 7S - Askafi, Eka; Sukamtono, Ali (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary Sciences, 2020)
An activity to be able to produce maximum results requires an established framework of thinking that is often called a paradigm. The last quarter century of the development of science and technology is very fast and difficult to estimate. The impact of the development of science and technology reaches various fields including economics. In this case the Islamic world in general is left behind by the West. This lag is partly due to the absence of a sophisticated and reliable paradigm of mindset. For this reason, a new paradigm needs to be built that is intact and easily understood, especially in managing the Islamic economy. First, there are four systemic words in management, namely (smart- S ), say (talk- T ), action ( A -action), and outcome ( R -result); abbreviated to STAR . Second, the expected outcome must be based on the three words that are the aim of the activity, in particular the Islamic Economy, namely the G old of wealth, the G ospel (success) which means the throne, and the G od (God) which is heaven; shortened to 3G . To get all three is required 7 (seven) Steps as taught by Allah in the Quran or Al-Fatihah which consists of repeated verses (QS, 15:87). God willing with the discovery of this new paradigm of the STAR 3G 7S will facilitate the understanding of Muslims in their identity, and will soon come out of shock and pursuit of loss.